2001
DOI: 10.1161/01.cir.103.4.525
|View full text |Cite
|
Sign up to set email alerts
|

Association of Thrombospondin-1 and Cardiac Allograft Vasculopathy in Human Cardiac Allografts

Abstract: Persistent elevation of TSP-1 in cardiac allografts correlates with the development of CAV. Allogeneic stimulation induces angiogenic growth factors and TSP-1 in T cells. Cytokines differentially regulate TSP-1 expression in SMCs versus endothelial cells. Increased levels of TSP-1 in human cardiac allografts may alter vascular responses to angiogenic growth factors by inhibiting angiogenesis and promoting SMC proliferation characteristic of CAV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 24 publications
1
45
0
Order By: Relevance
“…This pattern is also similar to those observed for fibroblast growth factor (FGF) 19 and thrombospondin-1 (TSP-1). 20 In these studies, longitudinal analysis of FGF demonstrated that heart transplant recipients with late, elevated levels of FGF had an increased severity of CAV, whereas recipients who had low levels of FGF generally had no or mild CAV. A comparable observation was found with TSP-1, in that patients who had an initial elevation of TSP-1 followed by baseline levels had less severe CAV.…”
Section: Discussionmentioning
confidence: 98%
“…This pattern is also similar to those observed for fibroblast growth factor (FGF) 19 and thrombospondin-1 (TSP-1). 20 In these studies, longitudinal analysis of FGF demonstrated that heart transplant recipients with late, elevated levels of FGF had an increased severity of CAV, whereas recipients who had low levels of FGF generally had no or mild CAV. A comparable observation was found with TSP-1, in that patients who had an initial elevation of TSP-1 followed by baseline levels had less severe CAV.…”
Section: Discussionmentioning
confidence: 98%
“…NE results were normalized to the GAPDH result from the same reaction. 23 RNA from HL60 cells and fibroblasts served as a positive and negative control, respectively. …”
Section: Reverse Transcriptase-polymerase Chain Reactionmentioning
confidence: 99%
“…Later studies showed that during the allogeneic response in vitro, T lymphocytes produce angiogenic growth factors including VEGF. 17,18 Thus, the observations of Nykänen et al 13 may have particular relevance to this special form of arteriosclerosis. In addition to angiopoietin, transplanted hearts can overexpress another endogenous modulator of angiogenesis.…”
Section: See P 1308mentioning
confidence: 96%
“…These data suggest that angiogenesis modulators, such as TSP-1, inhibit angiogenesis and promote smooth muscle cell proliferation, processes that promote transplantation arteriopathy. 18 What lessons can we draw from the tale of transplantation arteriopathy? First, the life-saving procedure of cardiac transplantation comes with a biological cost -a risk of obliterative arteriopathy -that too often replaces one disease with another.…”
Section: See P 1308mentioning
confidence: 99%